An evolutionary analysis of antigen processing and presentation across different timescales reveals pervasive selection. - Diego Forni; Rachele Cagliani; Claudia Tresoldi; Uberto Pozzoli; Luca De Gioia; Giulia Filippi; Stefania Riva; Giorgia Menozzi; Marta Colleoni; Mara Biasin; Sergio Lo Caputo; Francesco Mazzotta; et al. (PLoS Genetics)
The antigenic repertoire presented by MHC molecules is generated by the antigen processing and presentation (APP) pathway. We analyzed the evolutionary history of 45 genes involved in APP at the inter- and intra-species level. Results showed that 11 genes evolved adaptively in mammals. Several positively selected sites involve positions of fundamental importance to the protein function (e.g. the TAP1 peptide-binding domains, the sugar binding interface of langerin, and the CD1D trafficking signal region). In CYBB, all selected sites cluster in two loops protruding into the endosomal lumen; analysis of missense mutations responsible for chronic granulomatous disease (CGD) showed the action of different selective forces on the very same gene region, as most CGD substitutions involve aminoacid positions that are conserved in all mammals. As for ERAP2, different computational methods indicated that positive selection has driven the recurrent appearance of protein-destabilizing variants during mammalian evolution. Application of a population-genetics phylogenetics approach showed that purifying selection represented a major force acting on some APP components (e.g. immunoproteasome subunits and chaperones) and allowed identification of positive selection events in the human lineage. We also investigated the evolutionary history of APP genes in human populations by developing a new approach that uses several different tests to identify the selection target, and that integrates low-coverage whole-genome sequencing data with Sanger sequencing. This analysis revealed that 9 APP genes underwent local adaptation in human populations. Most positive selection targets are located within noncoding regions with regulatory function in myeloid cells or act as expression quantitative trait loci. Conversely, balancing selection targeted nonsynonymous variants in TAP1 and CD207 (langerin). Finally, we suggest that selected variants in PSMB10 and CD207 contribute to human phenotypes. Thus, we used evolutionary information to generate experimentally-testable hypotheses and to provide a list of sites to prioritize in follow-up analyses.